Synthesis and Characterization of Ni/Hydrotalcite and Its Application in Hydrocracking Calophyllum Inophyllum Oil - Hafshah Hafshah; Danawati Hari Hari Prajitno; Achmad Roesyadi (The Journal of Pure and Applied Chemistry Research, 2016)
This research aims to synthesize hydrotalcite as an alternatives of catalyst support of hydrocracking of vegetable oils. Hydrotalcite can be synthesized in several ways, the most common is coprecipitation method. Hydrotalcite was synthesized using Mg/Al mole ratio of 1: 1, NaOH and Na2CO3 as base solutions. Ni/hydrotalcite catalyst was synthesized by incipicient wetness impregnation method with Ni impregnation of 10% w/w. The characterization of the crystal structure was determined by X-ray diffraction (XRD). The spesific surface area (SBET) was determined by adsorption-desorption of nitrogen, it were obtained 201 m2/g after impregnation and 191 m2/g before impregntion. The test of performance of catalyst was conducted by hydrocracking reaction of Calophyllum  inophyllum oil. The liquid products were analyzed by gas chromatography mass spectrometry (GC-MS). Hydrocracking process produced gasoline, kerosene, gas oil with yield of 0.36%, 2.45%, 54.88% respectively, conversion of 96.26% and selectivity of  gas oil of 84.39%.